Less Surface Sea Ice Melt in the CESM2 Improves Arctic Sea Ice Simulation With Minimal Non‐Polar Climate Impacts. (12th April 2022) - Kay, Jennifer E.; DeRepentigny, Patricia; Holland, Marika M.; Bailey, David A.; DuVivier, Alice K.; Blanchard‐Wrigglesworth, Ed; Deser, Clara; Jahn, Alexandra; Singh, Hansi; Smith, Madison M.; Webster, Melinda A.; Edwards, Jim; et al.
Abstract: This study isolates the influence of sea ice mean state on pre‐industrial climate and transient 1850–2100 climate change within a fully coupled global model: The Community Earth System Model version 2 (CESM2). The CESM2 sea ice model physics is modified to increase surface albedo, reduce surface sea ice melt, and increase Arctic sea ice thickness and late summer cover. Importantly, increased Arctic sea ice in the modified model reduces a present‐day late‐summer ice cover bias. Of interest to coupled model development, this bias reduction is realized without degrading the global simulation including top‐of‐atmosphere energy imbalance, surface temperature, surface precipitation, and major modes of climate variability. The influence of these sea ice physics changes on transient 1850–2100 climate change is compared within a large initial condition ensemble framework. Despite similar global warming, the modified model with thicker Arctic sea ice than CESM2 has a delayed and more realistic transition to a seasonally ice free Arctic Ocean. Differences in transient climate change between the modified model and CESM2 are challenging to detect due to large internally generated climate variability. In particular, two common sea ice benchmarks—sea ice sensitivity and sea ice trends—are of limited value for comparing models with similar global warming. More broadly, these results show the importance of a reasonable Arctic sea ice mean state when simulating the transition to an ice‐free Arctic Ocean in a warming world. Additionally, this work highlights the importance of large initial condition ensembles for credible model‐to‐model and observation‐model comparisons. Plain Language Summary: Satellite observations available from 1979 to present show dramatic Arctic sea ice loss. As a result, projecting when the Arctic Ocean may become ice free and the resulting impacts is of broad interest to those living in the Arctic and beyond. Climate models are the main tool for making such future projections. Yet, projecting sea ice loss is hard because it is affected by multiple factors that are often impossible to disentangle including physical processes, unpredictable climate variability, and differences in climate drivers. Unique to this work, we analyze the influence of the sea ice surface melt while also controlling for all other confounding factors such as the amount of global warming and unpredictable climate variability. Our work demonstrates that under similar global warming, surface melt affects the timing of an ice‐free Arctic Ocean. Specifically, simulations with less surface melt and more sea ice transition to an ice‐free Arctic Ocean later. From the perspective of model development and transient climate change, we also found sea ice amounts and the timing toward an ice‐free Arctic have negligible influence on warming, precipitation, and sea level pressure outside of the polar regions. Key Points: Decreasing surface melt decreases late‐summer Arctic sea ice cover biases and delays transition to an ice‐free Arctic Ocean Internal variability limits value of sea ice trends and sea ice sensitivity as metrics to constrain model performance under similar global warming Increasing sea ice thickness and area has negligible impacts on non‐polar climate and climate change